Espaço Cores: espaço de auxílio ao desenvolvimento de crianças com Transtorno do Espectro Autista (TEA) - Falcone, Giovanna Robert (Brasil, 2025)
This work aims to design a Support Space for the Development of Children with Autism Spectrum Disorder (ASD), with the proposal of centralizing, in a single location, areas dedicated to the main therapeutic demands, providing support for children diagnosed with ASD and their families. The theoretical framework will address the main theories and approaches that have contributed to the understanding of childhood autism, as well as a historical overview demonstrating the evolution of knowledge about this condition over time, consolidating contemporary practices. Furthermore, case analyses will be conducted to deepen the understanding of the subject and identify elements that can be applied to the proposed project. In addition, a survey of the area designated for the project's implementation will be carried out. The site is located in the city of Manaus, in the Aleixo neighborhood, South-Central region, specifically in the Morada do Sol complex. Based on the survey, maps related to land use and occupation, environmental conditions, zoning regulations, and the road system will be analyzed. Using this data, the architectural project will be developed, including floor plans, layouts, sections, facades, elevations, perspectives, and illustrative images, which aim to present the proposals clearly and in detail.